Pengaruh Struktur Modal, Rasio Aktivitas, Ukuran Perusahaan, Rasio Likuiditas, Terhadap Nilai Perusahaan Pada Perusahaan Penghasil Bahan Baku Sektor Pertanian Di Bursa Efek Indonesia (BEI) - Tasya Febri Sihombing; Wirda Lilia; Natalia Perangin Angin; Desi Fintaria Magdalena Sitorus; Veramika Sembiring (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Currently, the development of business competition is so tight, companies must develop their performance in order to stay afloat and can achieve their goals, namely seeking profits. The purpose of this study is to analyze the Effect of Capital Structure, Activity Ratio, Company Size, and Liquidity Ratio to Value of Agricultural Sector Raw Material Producing Companies listed on the Indonesia Stock Exchange. The research for this company used purposive sampling techniques, the number of samples obtained by 51 companies producing raw materials in the agricultural sector listed on the Indonesia Stock Exchange (IDX). hypothesis testing in this study, Partial and simultaneous results were found. Partial results in the research that has been carried out are the variables Capital Structure, Activity Ratio, Company Size. which has an effect on the value of the company. As for the simultaneous results, namely the Capital Structure variable, Activity Ratio, Company Size and Liquidity Ratio affect the Company Value variable in Agricultural Sector Raw Material Producing Companies on the Indonesia Stock Exchange. Keywords : Capital Structure, Activity Ratio, Company Size, Ratio Liquidity, and Company Value.